Re-framing European Union (EU) - United Kingdom (UK) Cooperation to Address Human Trafficking and Migrant Smuggling - Ventrella, Matilde; Morano Foadi, Sonia (Border Crossing, 2025)
Since the UK’s departure from the EU, the two parties have established a Trade and Cooperation Agreement (TCA) to shape their post-Brexit trade relationship. However, no formal agreement has been reached to address people smuggling and human trafficking, despite the UK government's stated intention to collaborate with the EU in tackling these crimes. We argue that when such an agreement is negotiated, it should adopt a human rights-based approach, ensuring the effective identification and protection of actual and potential victims of human trafficking. Enhanced cooperation in integrated border management, such as the 2024 post-Brexit arrangement between the European Border and Coast Guard Agency (Frontex) and the UK, and bilateral agreements with France, has yet to sufficiently prioritise human rights. Like the EU’s other cooperation agreements with third states, any potential future bilateral agreement should also incorporate human rights clauses, in line with specific measures contained in the TCA. These legally binding clauses are designed to safeguard and strengthen the protection of fundamental rights. Addressing the complexity of human trafficking and migrant smuggling, along with the multifaceted governance systems they entail, requires balancing the UK’s national sovereignty with the EU’s legal personality and primacy over its Member States in the development of bilateral agreements rooted in human rights. This challenge requires cooperation and responsibility-sharing, rather than uncoordinated systems that states, and non-state actors can exploit..